Differential Diagnosis of Leukocoria : A Case Report: Poster Presentation - Case Report - Resident - Rahman, Harrie Kurnia; Sayuti, Kemala (Majalah Oftalmologi Indonesia, 2023)
Introduction : Leukocoria is an abnormal pupillary reflex more clearly seen after mydriasis or photography. It is often the first sign of a range of serious intraocular disorders, including congenital cataracts, Coats disease, retinoblastoma, Familial Exudative Vitreoretinopathy (FEVR). Case Illustration : Baby F, 10 months with chief complaint the vision in both eyes appears defocused since birth. A history of trauma to the head is denied, severe pain (-), a history of similar complaints in the family is denied. Pregnancy history: Mother had hypertension. The patient born spontaneusly at 39-40 weeks of gestation, crying immediately, birth weight 2700 grams. Ophtalmology Status ODS: VA Blink reflex(+), Following light (+), Following object (-), Konjungtiva : hiperemis (-), cornea : clear (+), Pupil : leukocoria (+). Funduscopy examination ODS: Vitreus : cloudy (+), papillae: cannot be assessed, blood vessels: visible images of raised blood vessels, retina: detached (+) retinal layers seen, macula: cannot be assessed. USG ODS: cloudy vitreus with hyperreflectivity moderate to high. Patient was diagnosed with Leucocoria ec Retinal Detachment ec Suspect FEVR differential diagnosis Retinoblastoma Bilateral. CT Scan : A mass with a calcified component in the right and left posterior bulbs, consistent with bilateral retinoblastoma Discussion : The clinical history of leukocoria, meaning loss of the normal red retinal reflex, is nonspecific. Key findings here are the normal size of the globes and the presence of calcifications, which are more compatible with retinoblastoma, Coats' disease, or FEVR. Conclusion Leucocoria in aterm baby has several differential diagnosis such as retinoblastoma that needs further examination.